Bimbingan Karier dengan Teknik Modeling untuk Mengembangkan Kematangan Karier Peserta Didik - Shidratul Attika; Juntika Nurihsan; Amin Budiamin (Indonesian Counselor Association (IKI), 2020)
Career maturity is the readiness of an individual in choosing their career. This research aimed to examine the effectiveness of career guidance with modeling techniques to develop the students’ career maturity. This research implemented quasi-experimental research with nonequivalent control group design. Career maturity questionnaire was used as the research instrument. The participants consisted of nine experimental group students and nine control group students. The research samples were determined by implementing a purposive sampling technique. Data analysis used the Independent Sample T-Test. The results of data analysis showed the t value of 10.678 > t table 1.746, then the career maturity of the experimental group students after given career guidance intervention with modeling techniques was higher than the control group students who were not given intervention. It can be concluded that career guidance with modeling techniques effective to develop students' career maturity.